"We did not unleash this war. Our conscience is clear". The Russia–Ukraine military conflict and its perception in Belarus. (4th May 2022) - Mudrov, Sergei A.
ABSTRACT: This article analyses the response in Belarus to the Russia–Ukraine war, which started on 24 February 2022. Traditionally, the Belarusian president Alexander Lukashenko had been trying to maintain good working relations with Kiev, featuring Belarus as "the most reliable partner" of Ukraine. However, when Moscow launched its "special military operation" in Ukraine, Lukashenko chose to fully ally with Russia, allowing the free passage of the Russian Army through the territory of Belarus and the use of necessary infrastructure by Russian forces. In his justifications of the war, Lukashenko deliberated on themes such as regional security and possible threats from Ukraine. The state-controlled media have provided extensive explanations for the Moscow invasion, speaking about the necessity of settling the Donbas conflict, the aggressive policy of Kiev in relation to Belarus, the inadequate behaviour of Ukrainian elites, and the need for de-Nazification of Ukraine. The discordant voices were mainly coming from the opposition media, which had developed a pro-Ukraine narrative. Given a lack of reliable surveys, it is not possible to properly assess the attitude of the general public towards the war in Ukraine, although it is likely that most Belarusians would sympathize the Moscow's interpretations of events.